Integrated hierarchical macrostructures of flexible basalt fiber composites with tunable electromagnetic interference (EMI) shielding and rapid electrothermal response. (1st November 2021) - Yu, Jin; Cui, Zhonglan; Lu, Jiayu; Zhao, Jialong; Zhang, Yan; Fan, Gaoqing; Liu, Siyuan; He, Yibo; Yu, Yihao; Qi, Dongming
Abstract: Adjustable and durable EMI shielding fabrics with excellent mechanical performance are urgently required owing to the rapid growing of electronics in industrial, military and aerospace fields. Herein, a highly flexible and durable conductive basalt fabric (BF) composite was firstly fabricated by integrating Ti3 C2 Tx nanosheets and conformal natural rubber-Ti3 C2 Tx layer via a facile spray-drying method. The effects of the natural rubber outlayer with or without Ti3 C2 Tx nanosheets on the composite are examined to determine the optimal composition and structure. The Ti3 C2 Tx nanosheets form a continuous and compact nacre lamellar coating on the surface of the external BF fibers, resulting in the main EMI shielding function. Especially, the conductive natural rubber-Ti3 C2 Tx (TNR) outlayer could not only protect the inner Ti3 C2 Tx coating, but also form conductive connections between conductive BF fibers. The resultant EMI shielding basalt fabrics possess hierarchical macrostructures, which could even obtain an ideal EMI SE value of 41.53 dB. Besides, the TNR outlayer could also fasten the fabric structure and protect the conductive network, which led to negligible decreases after repeatedly bending to 10.0 mm radius for 200 cycles (99.0% retention), sonication for 30 min (98.8% retention) and peeling for 200 cycles (94.4% retention). Moreover, such fabrics also showed outstanding electro-thermal property. Even if applied a low voltage of 4 V, the temperature would immediately reach up to over 70 °C, which also possess excellent cycling stability. Consequently, this work reveals an effective and facial technology for preparing a much more competitive EMI shielding fabric. Graphical abstract: Image 1 Highlights: EMI shielding basalt fiber composites were developed with hierarchical structure. Multilayer coating was prepared by the spray-drying technique. The resultant textile possesses adjustable EMI shielding performance and rapid electrothermal response. The resultant textile exhibits superior durability under continous external forces.